Injection locking of violet laser diodes with a 3.2 GHz offset frequency for driving Raman transitions in 43Ca+. - Keitch, B; Thomas, N; Lucas, D (2013)
Two cw single-mode violet (397 nm) diode lasers are locked to a single external-cavity master diode laser by optical injection locking. A double-pass 1.6 GHz acousto-optic modulator is used to provide a 3.2 GHz offset frequency between the two slave lasers. We achieve up to 20 mW usable output in each slave beam, with as little as 25 μW of injection power at room temperature. An optical heterodyne measurement of the beat note between the two slave beams gives a linewidth of ≤10 Hz at 3.2 GHz. We also estimate the free-running linewidth of the master laser to be approximately 3 MHz by optical heterodyning with a similar device.